1993
DOI: 10.1007/bf02632144
|View full text |Cite
|
Sign up to set email alerts
|

Thermoxidative and hydrolytic changes in sunflower oil used in fryings with a fast turnover of fresh oil

Abstract: The modification of a sunflower oil used for 75 repeated deep‐fat fryings of potatoes, with a fast turnover of fresh oil during frying, was evaluated by measuring the total polar components isolated by column chromatography. The total polar components increased rapidly during the first 20 fryings from 5.09±0.21 (mean±SD) mg/100 mg unused oil to 15.99±0.40, followed by minor but also significant changes until the thirtieth frying (17.99±0.41 mg/100 mg oil). The level did not increase further with continued fryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
67
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 7 publications
20
67
0
1
Order By: Relevance
“…Quantitative results obtained for the main groups of glyceridic compounds indicate the primacy of the formation of polymerization compounds (TGD plus TGP) which contribution to polar compounds was normally higher than 50% (numbers into brackets in Tables I and II) and even surpassed 70% for the most altered sample (SO in Table II). These results are in good agreement with those reported for oils with similar levels of polar compounds having been subjected to thermoxidation or frying under very distinct conditions (Arroyo et al, 1992;Cuesta et al, 1993;Dobarganes et al, 1993;Márquez-Ruiz et al, 1995;Pozo-Díaz et al, 1995), thus indicating that the variables of the treatment affect mainly the total degradation level.…”
Section: Resultssupporting
confidence: 91%
“…Quantitative results obtained for the main groups of glyceridic compounds indicate the primacy of the formation of polymerization compounds (TGD plus TGP) which contribution to polar compounds was normally higher than 50% (numbers into brackets in Tables I and II) and even surpassed 70% for the most altered sample (SO in Table II). These results are in good agreement with those reported for oils with similar levels of polar compounds having been subjected to thermoxidation or frying under very distinct conditions (Arroyo et al, 1992;Cuesta et al, 1993;Dobarganes et al, 1993;Márquez-Ruiz et al, 1995;Pozo-Díaz et al, 1995), thus indicating that the variables of the treatment affect mainly the total degradation level.…”
Section: Resultssupporting
confidence: 91%
“…The results obtained from all of the above described experiences are in agreement with those found by different authors which reported an increase of the polar content with the number of fryings (Fedelli, 1988;Sánchez-Muniz etaL, 1989;Cuesta etaL, 1991;Cuesta etaL, 1993;Sánchez-Muniz, 1993).…”
Section: Changes In These Oil During Fryingsupporting
confidence: 91%
“…It is well discussed in the literature that formation of polymers is aggravated with increased frying temperature and total number of fryings. (Choe and Min 2007;Cuesta et al 1993). However, in the present study the significant increase (P<0.05) of viscosity in the intermittent frying oil is noteworthy and can be attributed to the fact that solubility of oxygen increases as the oil cools down from frying temperature (as discussed before).…”
Section: Resultssupporting
confidence: 56%